The relation of children’s shame-proneness to mothers’ cognitions, anxiety and control - Bilge, Sibel F. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2023., 2023)
Shame has been linked to adverse developmental outcomes, including behavior problems such as aggression, depression, and anxiety (Tangney & Dearing, 2002). Previous research suggests that parenting-related cognitions, emotions, and controlling practices are crucial in shaping shame-proneness in children (Mills, 2005). This study investigates the ways in which these factors are related to children’s shame-proneness during early childhood. Two parental control behaviors, mothers' autonomy supportive approaches and their evaluations during dyadic interactions with their children, are examined. Cognitive and emotional constructs of interest are maternal parenting self- efficacy belief, contingent self-worth, and anxiety. The research comprised two distinct studies: Study 1 utilized observational data collected from 50 preschoolers and their mothers during laboratory sessions, focusing on the observations of maternal parenting behaviors and children's expressions of shame. Study 2 involved focus group discussions and one-on-one interviews with 39 mothers to gather qualitative data Turkish mothers' perceptions of their children's shame experiences. In line with the study's predictions, higher levels of parenting self-efficacy belief were negatively associated with children's observed shame, while mothers’ anxiety positively predicted maternal reports of child shame. Contrary to the hypotheses, analyses of the quantitative data revealed an inverse association between maternal control and shame. This seemingly contradictory findings gained significance when examined in the context of the insights obtained from focus group discussions and interviews. The analysis of maternal responses indicated that participating mothers all of whom had either an upper middle or high socio- economic status adopted a parenting approach characterized by autonomy support and warmth, creating a supportive environment that encouraged children's expressions of shame.
Keywords: Shame in children.; Stigma (Social psychology); Parent and child.